METODE ELEMEN HINGGA UNTUK PREDIKSI DEFORMASI BENDA KERJA DAN GAYA REAKSI DALAM SISTEM FIXTURE-BENDA KERJA - Tauviqirrahman, Mohammad; Munadi, Munadi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2007)
Knowledge of workpiece deformation and locator reaction forces in the fixture-workpiece system are essentialfor machining surface error prediction. Suitable methods for accurately predicting such deformations and forces areessential to the design and operations of fixtures. In this regard, researches based finite element analysis in fixturinghas been widely applied by researchers. A finite element (FE) model of the fixture-workpiece system is well-suited forpredicting workpiece deformation and reaction forces. However, these studies generally neglect the effects of differentfinite element model parameters on workpiece deformation. This study uses finite elemet method (FEM) to model afixture-workpiece system and to explore the effects of certain finite element model parameters on the prediction. Inaddition, this effects on the prediction accuracy are also examined. Based on this study, the workpiece deformationsand locator reaction forces predicted by the FEM model shows agreement within 3-4 % of the experimental data.